Respuesta :
The equation given in the question has one unknown variable in the form of "x" and only one equation is required to find the value of the unknown variable. So it is absolutely possible to find the exact value of "x".
6(-3 - x) - 2x = 14
-18 - 6x - 2x = 14
-18 - 8x = 14
Multiplying both sides of the equation by -1 we get
8x + 18 = - 14
Dividing both sides by 2 we get
4x + 9 = - 7
4x = - 7 - 9
4x = - 16
x = - 16/4
= - 4
So the value of "x" comes out to be equal to - 4. I hope the procedure is clear enough for you to understand.
6(-3 - x) - 2x = 14
-18 - 6x - 2x = 14
-18 - 8x = 14
Multiplying both sides of the equation by -1 we get
8x + 18 = - 14
Dividing both sides by 2 we get
4x + 9 = - 7
4x = - 7 - 9
4x = - 16
x = - 16/4
= - 4
So the value of "x" comes out to be equal to - 4. I hope the procedure is clear enough for you to understand.
Let's solve your equation step-by-step:
It's usually easier to rewrite the equation, so let's do that
6(-3-x)-2x = 14
Step 1: Simplify both sides of the equation.
6(-3-x)-2x = 14
Simplify: (Distribute)
(6)(-3)+(6)(-x)+-2x=14
-18+-6x-2x = 14
(-6x + -2x) + (-18) = 14
(Combine like terms)
-8x+-18 = 14
-8x - 18 = 14
Step 2: Add 18 to both sides
-1x-18+18 = 14+18
-8x = 32
Step 3: Divide both sides by -8
-8x/8 = 32/-8
x = -4
Final answer -
x = -4
You can check your work by replacing your x by -4 so your equation will equal 14. Remember, use PEMDAS or your answer will not come out correctly.
↑ ↑ ↑ Hope this helps! :D